Directors’ Duties and the Collective Governance of Algorithmic Management Systems - Salazar V, Alberto (McGill Law Journal / Revue de droit de McGill)

(untitled) (McGill Law Journal / Revue de droit de McGill, 2024)
While algorithmic management has improved corporate performance, it poses potential harm to workers and may jeopardize the long-term sustainability of companies, warranting regulatory intervention. Ex-ante human rights impact assessment of algorithmic management systems (AMS) is critical and has been widely adopted. The impact of AMS on multiple stakeholders, the shared ownership of workplace data, and the need to enhance AMS assessments’ quality and legitimacy may justify the adoption of a collective or multi-stakeholder governance of algorithm assessment. However, many jurisdictions have not embraced this approach. In countries with a shareholder primacy tradition, governance structures for ex-ante AMS assessments often exclude workers from having a voice in the assessment process. Even in jurisdictions adhering to stakeholder-oriented corporate governance models where worker participation in AMS governance is permitted, corporate resistance can significantly hinder such involvement. This paper argues that consideration should be given to expanding directors’ duties, requiring them to collaborate with the AMS assessment process and its collective governance, including facilitating workers’ involvement. Directors’ collaborative duties may help remove significant barriers by obligating them to disclose, coordinate, negotiate, and rectify workplace algorithms to serve the interests of companies and multiple stakeholders, including safeguarding workers’ human rights. The effectiveness of this multi-stakeholder governance of AMS assessments requires directors’ collaborative duties, which can help build efficient, equitable, and sustainable AMS.